Effect of Erythromycin Analogues on Binding of [(14)C]Erythromycin to Escherichia coli Ribosomes - Pestka, Sidney (1974)
The relative ability of 44 erythromycin analogues to bind to ribosomes was determined by their effect on [(14)C]erythromycin binding to Escherichia coli ribosomes. The association and dissociation constants of each of these erythromycin derivatives were determined as well as their interaction coefficient for their binding to ribosomes. Substitutions were made on various portions of the erythromycin molecule with retention of substantial activity as measured by inhibition of [(14)C]erythromycin binding to ribosomes. Since the effect of erythromycin analogues on [(14)C]erythromycin binding to ribosomes provides a relatively sensitive assay for these compounds, erythromycin analogues with relatively little affinity for ribosomes could be detected. Compounds with association constants of 10(4) M(−1) were detectable; the association constant for erythromycin binding to ribosomes was approximately 10(8) M(−1). Thus, compounds with 0.0001 the association constant of erythromycin were detectable. This assay could be used alone or in conjunction with microbiological assays for primary screening of active analogues or other compounds which interfere with [(14)C]erythromycin binding to ribosomes. It permits an estimate of the general activity of compounds rapidly and directly. Variables such as metabolic modifications of the compounds and permeability are excluded. The present assay reflects the ability of the compounds to interact directly with their target organelle and may serve as a useful adjunct in developing new compounds.